Wider Caribbean in the 20th century : a long-run development perspective (2001)
Explores long-run development patterns in the wider Caribbean over the last 100 years. Uses a specially constructed database for 28 Caribbean countries divided into two time periods : 1900-60 and 1960-98.
Bibliography: p. 56